Liminal Readings: Framing Strategies in Selected Romantics Texts - Wall, Shelley (My University, 1996)
This thesis explores narrative framing strategies in five Romantic texts: Wordsworth's The Ruined Cottage. Coleridge's Kubla Khan and an episode from Chapter Six of Biographia Literaria, Shelley's Julian and Maddalo, and Keats's The Fall of Hyperion. Using Freud's analysis of "the uncanny" and Alice Jardine's conception of "gynesis" as key elements, the introductory chapter proposes a view of "framing" as a strategy of interpretive and narrative control aligned with culturally masculine ideals of mastery and authority while identifying that which is represented within the frame as manifesting a strange alterity, often coded as feminine, which exceeds the terms established in the framing argument. Within this type of framing structure, Romantic anxieties about the authority of the writing subject play themselves out. The texts by Wordsworth, Coleridge and Shelley studied here exemplify framing as a strategy to control interpretation of a polysemous interior discourse. Keats's text furnishes a counter-example, deploying the apparatus of the interpretive frame only to subvert its conventions. Barthes's distinction between texts of "pleasure" and of "bliss" contributes to an understanding of the contrast between representations of textual closure and textual openness.
Keywords: English Language and Literature; English Language and Literature